Fluorescent intracellular imaging of reactive oxygen species and pH levels moderated by a hydrogenase mimic in living cells - Xin-Yuan Hu; Jia-Jing Li; Zi-Wei Yang; Jun Zhang; Huai-Song Wang (Elsevier, 2022)
The catalytic generation of H2 in living cells provides a method for antioxidant therapy. In this study, an [FeFe]-hydrogenase mimic [Ru + Fe2S2@F127(80)] was synthesized by self-assembling polymeric pluronic F-127, catalytic [Fe2S2] sites, and photosensitizer Ru(bpy)32+. Under blue light irradiation, hydrated protons were photochemically reduced to H2, which increased the local pH in living cells (HeLa cells). The generated H2 was subsequently used as an antioxidant to decrease reactive oxygen species (ROS) levels in living cells (HEK 293T, HepG2, MCF-7, and HeLa cells). Our findings revealed that the proliferation of HEK 293T cells increased by a factor of about six times, relative to that of other cells (HepG2, MCF-7, and HeLa cells). Intracellular ROS and pH levels were then monitored using fluorescent cell imaging. Our study showed that cell imaging can be used to evaluate the ability of Ru + Fe2S2@F127 to eliminate oxidative stress and prevent ROS-related diseases.